PENGARUH MEDIA TANAM TERHADAP PERTUMBUHAN SETEK MIKRO KENTANG VARIETAS GRANOLA (Solanum Tuberosum L) - EFRIANA JON (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2018)
Potato (Solanum tuberosum L) isan agricultural crop that has high economic value, it gets priority to be developed. This research at wasconductedScreen House of Balai Benih Induk Kentang (BBIK) Kayu Aro subdistrict Kerinci regency.The purpose of this research was to know the effect of planting media On Micro Cutting Growth Of Granola Potato Variety (Solanum Tuberosum L). This study was used Completely Randomized Design (RAL) with 6 Treatment 10 Deuteronomy. The observed parameters were percentage of live micro cuttings potato, the high micro cuttings, number of shoots, numbr of leaves, and length of rootwere analyzed by the variance of investigation and followed by DNMRT advanced test at 5% level. The investigation result of the highest percentage (%)of micro cutting potato live was 90%. The High of micro cuttings, number of shoots and number of leaves of micro cuttings granola varieties was showed that no significant effect on the treatment given. Whereas for the root length of micro cuttings showed thatthere was a significantly different effect.